Our Own Image : A Story of a Maori Filmmaker - Barclay, Barry (Book collections on Project MUSE., 2015)
Acclaimed Maori filmmaker Barry Barclay's 'Our Own Image' relates the experiences of making his documentaries and his critically acclaimed feature-length film Ngati (1987), widely credited as the first fiction feature by a member of an indigenous community. Barclay details his views on the process of filmmaking within his own Maori community and discusses how his work differed from popular cinema, advocating for indigenous control, participation, and perspectives in media.